The Practicality and Effectiveness of the Physics Independent Learning (PIL) Model Toolkit in Online Tutorials to Improve Physics Independent Learning Skills and Physics Problem-Solving Skills - Paken Pandiangan (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to analyze the practicality and effectiveness of the PIL model tool in online tutorials to improve self-learning and problem-solving skills in DL physics students in introductory quantum physics courses. This type of research is educational development research with a sample of 75 undergraduate physics education students at Universitas Terbuka in Indonesia. This research was carried out in three stages, namely preliminary and development studies, limited trials, and extensive trials. The results showed that tutors could carry out all stages of online tutorial activities using the PIL model very well with the percentage of implementation of syntax, social systems, and reaction principles. There was an increase in students' problem-solving abilities and independent learning abilities in each class after taking PIL with high N-gain categories. It can be concluded that the PIL model set is valid, practical, and effectively applied to improve problem solving skills and students' independent skills in learning Introduction to Quantum Physics.